Peran Kepolisian Dalam Penegakan dan Penanggulangan Tindak Pidana Narkoba Terhadap Pengguna di Wilayah Hukum Kepolisian Resorkota Besar Medan - Jonathan Hasudungan Hasibuan; Suhaidi Suhaidi; Alvi Syahrin; Mahmud Mulyadi (USU LAW JOURNAL, 2019)
Abstract. Medan City Big Police Resort (Polrestabes) part of the Republic of Indonesia National Police located in the city of Medan, North Sumatra province is one of the regional units under the control of the North Sumatra Regional Police (North Sumatra Regional Police). Medan Polrestabes in combating Narcotics-related crime cases must be well supported even though the numbers of these cases continue to increase. The disclosure of cases on the one hand can indeed be an indicator of increasing police work in hunting down drug trafficking syndicates, but on the other hand can provide clues to how the current government policies are weak in dealing with the circulation. Police efforts as law enforcement agencies in preventing and eradicating Narcotics crime in the jurisdiction of Medan Polrestabes can be seen from the performance of its ranks who are actively both open and closed, cooperating with other agencies and communities in breaking the chain of Narcotics circulation. Medan Polrestabes in this case has two steps to prevent and eradicate this Narcotics and Psychotropic crime, namely the efforts of Non-Penal and Penal's efforts. The police maximize the Non-Penal efforts, namely pre-eminent and preventive measures (prevention), because these efforts are considered more effective in suppressing the increase in the number of criminal acts Narcotics compared to the efforts of Penal (prosecution). Keywords : police, narcotics, and narcotics crime